2019
DOI: 10.1016/j.jval.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Computed Tomography- Versus Ultrasound-Guided Percutaneous Radiofrequency Ablation Among Medicare Patients 65 Years of Age or Older With Hepatocellular Carcinoma

Abstract: Background: For patients with hepatocellular carcinoma (HCC) not eligible for surgical resection, radiofrequency ablation (RFA) is a promising technique that reduces the risk of disease progression. Objectives: To evaluate whether the trend of image guidance for RFA is moving toward the more expensive computed tomography (CT) technology and to determine the clinical benefits of CT guidance over the ultrasound (US) guidance. Methods: A cohort of 463 patients was identified from the Surveillance, Epidemiology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
(25 reference statements)
3
12
1
Order By: Relevance
“…In our analysis, we prospectively compared the effectiveness and safety of US, CT, and combinationguided percutaneous MWA in treating patients with HCC. The local recurrence and grade C complication rates were not signi cantly different between patients with CT and US-guided MWA, which was consistent with the ndings of a previous related study [14,21]. US has the advantages of real-time monitoring, a short operation time, and a clear display of blood vessels and the bile duct, while CT has a high accuracy of puncture and a high image resolution [3,4].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our analysis, we prospectively compared the effectiveness and safety of US, CT, and combinationguided percutaneous MWA in treating patients with HCC. The local recurrence and grade C complication rates were not signi cantly different between patients with CT and US-guided MWA, which was consistent with the ndings of a previous related study [14,21]. US has the advantages of real-time monitoring, a short operation time, and a clear display of blood vessels and the bile duct, while CT has a high accuracy of puncture and a high image resolution [3,4].…”
Section: Discussionsupporting
confidence: 88%
“…However, the limited literature comparing the thermal ablation of HCC under the guidance of CT and US has shown that both of these techniques have excellent outcomes [14]. It is worth noting that the postprocedural complication rates of thermal ablation vary greatly, from 2.2% to 53.2% [14,15]; we cannot say that this is not in uenced by the method of imaging guidance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The median follow-up period was 14 (12)(13)(14)(15)(16)(17)(18)(19)(20) months. During the follow-up period, 8 patients (combination group: 2 patients, CT group: 2 patients, US group: 4 patients) experienced local recurrence and received repeat MWA, and the local recurrence rates were 5.9%, 6.7%, and 16.7% in the combination group, CT group, and US group, respectively.…”
Section: Clinical E Cacymentioning
confidence: 99%